2012
DOI: 10.1002/fam.1124
|View full text |Cite
|
Sign up to set email alerts
|

Fire behaviour and external flames in corridor and tunnel‐like enclosures

Abstract: This work investigates how the inflow, the burning and the outflow develop in a corridor open to one end having a fire at either the closed or open end. The situation of a corridor fire having a fire source at the close end is a situation similar to a tunnel having a fire source at the centre of the tunnel without ventilation. A gaseous propane burner is used to produce the fire at a prescribed fuel flow rate in a long corridor of aspect ratio up to 6:1 having a rectangular cross section and varying door‐like … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
2
8
0
Order By: Relevance
“…The results of Prof. Delichatsios' studies support those of previous works on long corridors and tunnels. He concluded that the gas flow is controlled by different phenomena, distinguished in terms of the buoyancy source, including the following:horizontal gravity flow at open end of tunnel or corridor ,entrainment requirements of buoyant flow at source ,combustion air requirements of fire source andnature of fuel bed:For a gaseous burner having a fixed fuel‐supply rate, the flames move towards the open end.For solid or liquid fuel, the combustion is local if the spread of fuel is localised.For distributed solid or liquid fuel, the combustion moves towards the front of the fuel .…”
Section: Introductionsupporting
confidence: 86%
“…The results of Prof. Delichatsios' studies support those of previous works on long corridors and tunnels. He concluded that the gas flow is controlled by different phenomena, distinguished in terms of the buoyancy source, including the following:horizontal gravity flow at open end of tunnel or corridor ,entrainment requirements of buoyant flow at source ,combustion air requirements of fire source andnature of fuel bed:For a gaseous burner having a fixed fuel‐supply rate, the flames move towards the open end.For solid or liquid fuel, the combustion is local if the spread of fuel is localised.For distributed solid or liquid fuel, the combustion moves towards the front of the fuel .…”
Section: Introductionsupporting
confidence: 86%
“…Its aspect ratio is determined based on a survey of 17 urban road tunnels in Beijing, Nanjing and Shenzhen in China, and is considered to be an extensive representation [30] . The most widely used wall and ceiling materials for model tunnels is the fireproofing board [21,31,32] as it has low thermal conductivity which is a reasonable representative of real tunnel materials. Fireproofing boards of 20 mm thick were used to make the top, bottom and one sidewall of the tunnel while the other sidewall was made of 10 mm thick fire-resistant glass for observation.…”
Section: Introductionmentioning
confidence: 99%
“…Their work 1 proposed a model named the VU model, which can be used for the calculation of the HRR based on the enclosure geometry. They also compared the results of the VU model with that of the Conseil International du Batiment (CIB) model 1,5 Recently, a new version of FDS (version 6) 10 has been released with improved evaporation and combustion sub-models. Therefore, this study aims to redesign the experimental rig in which fire behaviour can be accurately simulated using FDS6.…”
Section: One Of the Benchmark Experimental Work Was Conducted Bymentioning
confidence: 99%
“…A series of small‐scale experiments with various enclosure sizes, locations of fire and geometries of opening were carried out in the study of Beji et al This study measured the HRR and combustion gases under a calorimeter hood as well as the temperature inside the enclosure using thermocouple trees at various locations. It is noted that the inflow rate of air and HRR was only affected by the shape of opening but not the length of the enclosure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation